Karel Wilms, één van de velen - Coenen, Armand; Clijmans, Willy; Francken, Fritz (Antwerpen : Van Uffelen & Delagarde, 1945)
Bibliotheek Camille Huysmans
Nederlands
Monografie
Keywords: Wereldoorlog 2; verzetsbeweging; Antwerpen